2012
DOI: 10.3174/ajnr.a3289
|View full text |Cite
|
Sign up to set email alerts
|

Multicontrast MR Imaging at 7T in Multiple Sclerosis: Highest Lesion Detection in Cortical Gray Matter with 3D-FLAIR

Abstract: BACKGROUND AND PURPOSE:7T MR imaging has led to improved detection and classification of cortical MS lesions, mainly based on T2*-weighted gradient-echo sequences. Depiction of cortical GM by using the recommended MS imaging protocol has not yet been investigated at 7T. We aimed to investigate prospectively which recommended sequence for clinical use has the highest value at 7T, in terms of GM and WM lesion detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…18 This finding was supported by another study in which DIR detected 43% more cortical lesions than FLAIR. 9 However, a study from Kilsdonk et al 28 at ultra-high-field strength (7T) showed that FLAIR detected 89% more cortical lesions than DIR, and that DIR and T2WI obtained nearly identical mean cortical lesion counts (115 versus 116). This finding indicates that a sequence that may be optimal at a lower field strength (DIR at 3T) may lose its benefit at a higher field strength (7T), and vice versa: A sequence suboptimal at a lower field strength may have an advan- Note:-WM-WML indicates white matter-to-white matter lesion CNR; GM-GML, gray matter-to-gray matter lesion CNR; GM-WM, gray matter-to-white matter CNR.…”
Section: Discussionmentioning
confidence: 99%
“…18 This finding was supported by another study in which DIR detected 43% more cortical lesions than FLAIR. 9 However, a study from Kilsdonk et al 28 at ultra-high-field strength (7T) showed that FLAIR detected 89% more cortical lesions than DIR, and that DIR and T2WI obtained nearly identical mean cortical lesion counts (115 versus 116). This finding indicates that a sequence that may be optimal at a lower field strength (DIR at 3T) may lose its benefit at a higher field strength (7T), and vice versa: A sequence suboptimal at a lower field strength may have an advan- Note:-WM-WML indicates white matter-to-white matter lesion CNR; GM-GML, gray matter-to-gray matter lesion CNR; GM-WM, gray matter-to-white matter CNR.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging sensitive to cortical lesions has revealed their absence in NMO (excluding one Japanese study of NMO pathology 48 ), whereas they are seen in the majority of patients with MS. 49,50 Characteristic MS brain lesions surround central venule in .80% on high-strength MRI. 50,51 In NMO lesions, this is less frequent, reported in 9% to 35% of cases 50,52 and likely indicates the different pathogenic mechanisms of the disease.…”
Section: Comparing the Imaging Of Nmosd Withmentioning
confidence: 99%
“…8). 43,44 Cortical lesions are rather specific for multiple sclerosis (MS), and they occur in the earliest stages of the disease. 50 It is clinically important to make cortical lesions visible in vivo by clinical 3D MR imaging.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…For 3D-FLAIR, there are many reports regarding application to multiple sclerosis. 5,6,[42][43][44][45][46][47][48][49][50][51][52][53][54] Smaller lesions can be detected by 3D-FLAIR than by 2D-FLAIR due to thinner slices and fewer flow artifacts with 3D-FLAIR. 45,46 Excellent detection of cortical lesions by 3D-FLAIR has also been reported (Fig.…”
Section: Clinical Applicationsmentioning
confidence: 99%